Detection and Parameter Estimation of Multicomponent LFM Signal Based on the Cubic Phase Function. (26th May 2008) - Wang Wang, Yong Yong; Jiang Jiang, Yi-Cheng Yi-Cheng
Abstract : A new algorithm for the detection and parameters estimation of LFM signal is presented in this paper. By the computation of the cubic phase function (CPF) of the signal, it is shown that the CPF is concentrated along the frequency rate law of the signal, and the peak of the CPF yields the estimate of the frequency rate. The initial frequency and amplitude can be obtained by the dechirp technique and fast Fourier transform. And for multicomponent signal, the CLEAN technique combined with the CPF is proposed to detect the weak components submerged by the stronger components. The statistical performance is analyzed and the simulation results are shown simultaneously.